Avaliação da atividade mutagênica do resíduo sólido de uma fábrica de confecções de meias e lingerie em ensaios com Salmonella typhimurium - Varella, S. D. [UNESP]; Varanda, Eliana Aparecida [UNESP]; Pozetti, G. L. [UNESP]; Vilegas, Wagner [UNESP] (My University, 2003)
Cancer is one of the most hazardous effects to human health caused by the exposition to chemical agents. The search for new technological solutions in the industrial field led to a rapid increase in the productive sector, causing the workers to be exposed to millions of potentially toxic agents, substances potentially harmful to health. This study presents the mutagenic activity of sweepings from a sock and lingerie factory in Araraquara-Brazil, assayed with Salmonella typhimurium. All the extracts from the factory had mutagenic on activity the YG1024 strain, which is extremely sensitive to detect the mutagenic activity of the arilhydroxilamines, nitroarenes and aromatic amines. The extracts were non-mutagenics for the strains TA100 and TA98. The analysis of the mutagenicity of industrial residues is highly important because employees that participate in the production are directly exposed to those agents, as well as to the environment where the garbage is deposited.
Mutagenic activity of sweepings from a sock and lingerie factory assayed with Salmonella typhimurium
Keywords: Ames test; Industrial garbage; Mutagenicity; Occupational exposure; aromatic amine; aromatic nitro compound; hydroxylamine; Brazil; cancer; controlled study; dose response; industrial waste; mutagenicity; nonhuman; occupational exposure; Salmonella typhimurium; textile industry